Targeting the DNA damage response for patients with lymphoma: Preclinical and clinical evidences. (November 2020) - Carrassa, Laura; Colombo, Ilaria; Damia, Giovanna; Bertoni, Francesco
Graphical abstract: Highlights: Deregulation of DNA damage response mechanisms is frequent in lymphomas. DNA damage response defects can be exploited therapeutically in lymphoma. Preclinical and clinical data with CHK1, WEE1, ATR, DNA-PK and PARP inhibitors is shown. Abstract: The DNA damage response (DDR) is a well-coordinated cellular network activated by DNA damage. The unravelling of the key players in DDR, their specific inactivation in different tumor types and the synthesis of specific chemical inhibitors of DDR represent a new hot topic in cancer therapy. In this article, we will review the importance of DDR in lymphoma development and how this can be exploited therapeutically. Specifically, we will focus on CHK1, WEE1, ATR, DNA-PK and PARP inhibitors, for which preclinical data as single agents or in combination has been accumulating, fostering their clinical development. The few available clinical data on these inhibitors will also be discussed.